Institutional Quality and Macroeconomic Indicators on Foreign Direct Investment in Developing Asian Countries - Erlina, Serli; Nairobi; Sitorus, Nurbetty Herlina (Basecamp Economics PubMed, 2024)
This research endeavors to scrutinize the influence of institutional quality and macroeconomic factors on Foreign Direct Investment (FDI). The institutional quality dimensions analyzed include political stability and corruption, while the macroeconomic variables encompass Gross Domestic Product (GDP) and exchange rates. The study's sample comprises developing Asian nations over the period from 2012 to 2019. Employing a quantitative methodology, the study leverages panel data analysis to derive its findings. The results indicate that political stability and exchange rates do not exert a statistically significant effect on FDI. In contrast, corruption is found to have a negative and significant association with FDI, whereas GDP shows a positive and significant correlation. Based on these outcomes, it is advised that developing countries in Asia should prioritize the enhancement of institutional quality, particularly by mitigating corruption, as it poses a substantial impediment to FDI inflows. Future research is encouraged to refine the model by incorporating additional variables and employing dynamic panel data analysis to facilitate a more comprehensive exploration of the evolving interrelations among variables over time.